How open is open source: Software and beyond - Kerstin Balka; Christina Raasch; Cornelius Herstatt (Hamburg University of Technology (TUHH), Institute for Technology and Innovation Management (TIM), 2009)
Traditionally the protection of intellectual property is regarded as a precondition for value capture. The rise of open source (OS) software and OS tangible products, so-called open design, has challenged this understanding. Openness is often regarded as a dichotomous variable (open-source vs. closed-source) and it is assumed that online developer communities demand full opening of the product's source. In this paper we explore openness as a gradual and multi-dimensional concept. We conduct an Internet survey (N = 270) among participants of 20 open design communities in the domain of IT hardware and consumer electronics. We find that open design projects pursue complex strategies short of complete openness and that communities value openness of software more highly than openness of hardware. Our findings suggest that open design companies can successfully employ strategies of partial openness to safeguard value capture without alienating their developer community.
Keywords: 650